THE PERTURBATION TO NON-MARKOVIAN EQUATION OF MOTION CORRESPONDING TO COHERENT AND QUADRATURE NON-MARKOVIAN SSES - Hassan, N; Pourdarvish, A; Sadeghi, J (TWMS journal of applied and engineering mathematics, 2017)
In this paper, we derive the perturbation and post Markovian perturbation to non-Markovian equation of motion(NMEM) that correspond to coherent and quadrature non-Markovian stochastic Schrodinger equations (SSE). In that case, we derive two perturbation approaches for zero and first orders to the coherent and quadrature NMEM. In order to explain both approaches, we apply two examples of non-Markovian.Keywords: perturbation method, post Markovian perturbation method, non-Markovian equation of motion, probability operator, functional operator.AMS Subject Classification: 81V80, 60G15.